IX premio Lissone : 1955. - Premio Lissone 1955 (Lissone : Premio Lissone, 1955)
Bacci, Edmondo ; Baj, Enrico ; Basso, Guido ; Bergolli, Aldo ; Berti, Vinicio ; Birolli, Renato ; Borra, Pompeo ; Breddo, Gastone ; Capogrossi, Giuseppe ; Carmassi, Arturo ; Caruso, Dino ; Casorati, Francesco ; Ciangottini, G. ; Crippa, Roberto ; Dal Monte, M.G. ; Dangelo, Sergio ; etc.
IX premio Lissone : 1955, Austria - Belgio - Brasile - Germania - Francia - Italia - Olanda - Svizzera
boek